2016
DOI: 10.1016/j.socscimed.2016.02.040
|View full text |Cite
|
Sign up to set email alerts
|

When can parents most influence their child's development? Expert knowledge and perceived local realities

Abstract: Compelling evidence for the long-term impact of conditions in gestation and early childhood on both physical and psychosocial functioning and productivity has stimulated a focus in global health policy and social services on the “first 1000 days”. Consequently, related initiatives may assume that rationale for this orientation and the agency of parents during this period is self-evident and widely shared among parents and communities. We tested this assumption in 2012 among a sample of 38 township-dwelling car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 76 publications
0
20
0
1
Order By: Relevance
“…Thanks to a new generation of research, puberty is coming into focus as such a moment during which unique maturational milestones in physical, and consequently psychobehavioral, development are attained (Crone & Dahl, ). Although much of the pathbreaking work on sensitive periods, intergenerational transmission, and developmental origins of health and disease has focused on early life, particularly the “first thousand days” from gestation through infancy, many lines of evidence draw attention to puberty as a sensitive period of similar albeit distinctive importance (Scherf, Behrmann, & Dahl, ; Worthman, Tomlinson, & Rotheram‐Borus, ). Indeed, the emerging multidimensional biopsychobehavioral view of puberty plus recognition of the power of context in development blurs the distinction between puberty as a biological process and adolescence as a social construction, and foregrounds their biosocial, biocultural foundations.…”
Section: Theoretical and Conceptual Advancesmentioning
confidence: 99%
“…Thanks to a new generation of research, puberty is coming into focus as such a moment during which unique maturational milestones in physical, and consequently psychobehavioral, development are attained (Crone & Dahl, ). Although much of the pathbreaking work on sensitive periods, intergenerational transmission, and developmental origins of health and disease has focused on early life, particularly the “first thousand days” from gestation through infancy, many lines of evidence draw attention to puberty as a sensitive period of similar albeit distinctive importance (Scherf, Behrmann, & Dahl, ; Worthman, Tomlinson, & Rotheram‐Borus, ). Indeed, the emerging multidimensional biopsychobehavioral view of puberty plus recognition of the power of context in development blurs the distinction between puberty as a biological process and adolescence as a social construction, and foregrounds their biosocial, biocultural foundations.…”
Section: Theoretical and Conceptual Advancesmentioning
confidence: 99%
“…This negatively impacts parental nurturance, placing children at risk for poor development (Chaudry & Wimer, 2016; Roos et al, 2019). The emerging field of parenting research in SA has mainly focused on parenting styles (Makwakwa, 2011; Roman et al, 2016), parents' influence on child development (Worthman et al, 2016), the father–son relationship (Pitsoane & Gasa, 2018) and child homicide (Dekel et al, 2018). Because the study of nurturing parenting is not clear in the SA context, this study sought to explore and understand how parents nurture their children in RCE in SA.…”
Section: The Present Studymentioning
confidence: 99%
“…The economic prosperity of the region seems to add to the problem, since access to different types of screens influences people to stay indoors. Globally, studies have focused to find the association of parental PA and ST in relation to the age of adolescence, since the maximum influence of parents has been found to occur during adolescence [14]. A recent long term longitudinal study (30 years), however, has found that parental PA is associated with increased levels of children's physical activity till the age of 24 years, which tends to remain until their midlife, thus making the age category of young adults (18 to 35 years) very significant in tackling adult obesity [15].…”
Section: Introductionmentioning
confidence: 99%